“Everything was mute and calm; everything grey;” Benito Cereno, White Authority and #BlacklivesMatter - Catharine Shipps (The Journal of Undergraduate Research, 2016)
This paper examines how Herman Melville’s Benito Cereno presents the focalized perspectives of white authority figures in order to deconstruct different forms of racism, even from authority figures who exhibit sympathy for black slaves. I argue that Benito Cereno’s message resonates with the current efforts of activists to bring attention to the ways in which authority figures translate the activities of black citizens. America is increasingly debating the biases among our authority figures, specifically those involved in law enforcement. For instance, recent attention to law enforcement discrimination towards black Americans has spawned the group #BlackLivesMatter, which fights for justice in such cases. Benito Cereno is riddled with translations that create crises for the characters and readers forced to interpret ambiguous signals that serve to reveal their prejudiced perspectives. I suggest that the text, especially in its deposition section, undermines the authority of law enforcement narratives by subtly revealing the cultural biases that sometimes guide them.